How Medical Services Get Valued - Krol, Katharine L. (Seminars in Interventional Radiology, 2023)
The mechanisms for Medicare payment to physicians are complicated and, in fee for service Medicare, the value of a procedure code explicitly determines the payment to the physician and the out-of-pocket cost to the beneficiary. These codes are created and then valued for payment through a complex but reproducible and transparent process that allows for physician and specialty society input. This article describes the process and its implications for interventional radiology.
Keywords: relative value unit; CPT; procedure code; interventional radiology; Medicare; RUC; CMS